Action mechanism of araçá (Psidium cattleianum Sabine) hydroalcoholic extract against Staphylococcus aureus. (February 2020) - de Lima, Andréia Saldanha; Maia, Darla Volcan; Haubert, Louise; Oliveira, Thaís Larré; Fiorentini, Ângela Maria; Rombaldi, Cesar Valmor; da Silva, Wladimir Padilha
Abstract: Araçá ( Psidium cattleianum Sabine) is a native fruit of South America, with high levels of bioactive compounds as well as antimicrobial potential. The aim of this study was to evaluate the antibacterial activity of the hydroalcoholic extract of araçá (HEA) against Staphylococcus aureus and to evaluate its mechanism of action. HEA showed activity against S. aureus, with inhibition halos of 17 mm in diameter. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values were 9 mg mL −1 and 18 mg mL −1, respectively. The bacterial multiplication was inhibited by HEA exposure at the two concentrations evaluated (MIC and MBC), given that the microorganism was eliminated within 24 h of contact when the MBC was used. The bacterial cell membrane was compromised, losing its integrity, and releasing important cellular constituents. HEA also showed the ability to intercalate with bacterial DNA, indicating that its antistaphylococcal activity can occur in more than one target in the bacterium. The antistaphylococcal activity of HEA occurs by modification in cell membrane integrity and by causing damage to the DNA of S. aureus . This study shows promising and unpublished results and demonstrates that HEA has the potential to be used as a natural adjuvant in food preservation. Highlights: Hydroalcoholic extract of araçá (HEA) has antistaphylococcal activity. Release of important cellular constituents by HEA action. HEA showed ability to intercalate with bacterial DNA. HEA changes cell membrane integrity and causes damage in S. aureus DNA.